Carbohydrate ingestion and mouth rinsing on metabolism and endurance exercise performance. - Snyder, Brian S. (Kansas State University, 2011)
Maximizing performance and results in competitive events is something that all athletes strive to achieve. Nutritional strategies have been developed to best optimize the likelihood of success in competitive events. While dietary protein was classically believed to be the key macronutrient in exercise performance, overwhelming evidence now supports the role of maximizing carbohydrate intake and availability in endurance performance. The role of carbohydrate intake prior to, during and after endurance exercise has been heavily studied and relevant literature will be discussed herein. This paper consists of three chapters and a summary related to carbohydrate intake and performance outcomes in endurance sports. While nutritional status surrounding the endurance events is discussed, this paper focuses on the ergogenic and metabolic effects of carbohydrates during the endurance bout. Chapter one serves as a literature review of carbohydrate administration during endurance exercise. Types of carbohydrates, their role as substrates in liver and skeletal muscle during exercise, and their effects on endurance performance are discussed. The role of carbohydrate on central factors of fatigue and motor output also are covered. Chapter two addresses the role of multiple carbohydrate supplements on cycling performance. The role of these supplements on blood glucose, insulin, lactate, and IGFBP-1 also are discussed. Chapter three addresses the effect of nutritional status prior to exercise on the ability of a carbohydrate mouth rinse to impart a performance enhancing effect. There were no treatment effects (p>0.05) of the type carbohydrate ingested, compared with placebo, on selected metabolic and performance outcomes. Likewise, there was no ergogenic effect of mouth rinsing, in the fasted or fed state, in moderately trained endurance cyclists.
Keywords: Sports nutrition; Carbohydrate; Endurance exercise; Kinesiology (0575); Nutrition (0570)